THE EFFECT OF STORE ATMOSPHERE AND PEER PRESSURE ON PURCHASE INTENTION AT HOUSEPITALITY CAFÃ‰ AND RESTAURANT - Gonibala, Resila Quraisy; Tumewu, Ferdinand . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Nowadays, taste, price, service andquality of the food no longer being a major consideration for the customer. Company should be implementing the right strategy, new concept and also creative ideas to make consumer feel comfortable. One of the strategies is Store Atmosphere, when consumers get the experience in restaurant they will increase to purchase, revisit and Peer Pressure to others. Housepitality Cafe and Restaurant has unique concept and decor to make customer feel like dining inside a hospital instead of restaurant, the purpose of this study to determine the effect of Store Atmosphere and Peer Pressure either simultaneously or partially on Purchase Intention at Housepitality café and restaurant. The method used in this research is Multiple Linear Regression analysis. The study population were 60 respondents who live in the city of Manado. The results show Store Atmosphere and Peer Pressure simultaneously and partially influence on Purchase Intention. Housepitality must consider about importance and benefits of Peer Pressure and also evaluate Store Atmosphere to increase customers.Keywords: store atmosphere, peer pressure, purchase intention